Communicative Action: Correlation Of Leadership Principles In The Viewpoint Of Muhammad Rasulullah And J. Habermas - Hilabi, Igo Ilham; Saputra, Andhika Rahmat; Sa'diyah, Chalimatuz; Nurhasanah, Siti (Technium Social Sciences Journal, 2021)
This study aims to briefly review the thoughts of Jurgen Habermas, a German philosopher at the Frankfurt School with his critical philosophy, especially regarding social thought, by comparing it with the concept of spiritual leadership in Islam as reflected by the leadership characteristics of the Prophet Muhammad SAW. Data processing uses descriptive analysis with a deconstruction paradigm, looking more sharply to provide new and critical meanings to the interpretation of Habermas's thoughts. The text is understood and rearranged from a different point of view. After finding the philosophical foundation and structure of Habermas' thought, the researcher compares his thoughts to the concept correlation of the Leadership of the Prophet Muhammad SAW so as to find Habermas' intentions related to Communicative Action and the rational development of society. The results of this study prove that Habermas's idea has a similar concept to Islamic spiritual leadership in a brief conceptualization that reflects the character and values that adhere to humanity, equality of emancipatory values and prioritizing communication in deliberation and solidarity that can lead to great ideals Naturalism is welfare in Habermasian Communicative Action. The spiritual implications of Islamic leadership are addressed using a democratic method and prioritizing the social side so that it has a purpose for the development of society.